Pengukuran Beban Kerja Fisik dan Mental Pada Pekerja Menggunakan Metode Cardiovascular Load (CVL) dan NASA-TLX - Anwar, Arsya Amira; Yuamita, Ferida (nter of Execellence (COE) ICT Infrastructure, Smart Manufacture and Digital Supply Chain, 2024)
This study examines the effects of physical and psychological exhaustion on Balai P2P Jawa III employees, taking into account their age, gender, and way of life. The term